Biochemistry - Abali, Emine Ercikan; Cline, Susan D.; Franklin, David S. (Philadelphia : Wolters Kluwer, 2022)
Biochemistry is the study of how our bodies utilize the nutritional substances in our diet to make building blocks, fuels, and communication molecules for our cells. It also includes the processes by which we convert chemicals within our bodies and eliminate chemicals from our bodies--
Amino Acids and the Role of PH -- Protein Structure -- Globular Proteins -- Fibrous Proteins -- Enzymes -- Bioenergetics and Oxidative Phosphorylation -- Introduction to Carbohydrates -- Introduction to Metabolism and Glycolysis -- Tricarboxylic Acid Cycle and Pyruvate Dehydrogenase Complex -- Gluconeogenesis -- Glycogen Metabolism -- Monosaccharide and Disaccharide Metabolism -- Pentose Phosphate Pathway and Nicotinamide Adenine Dinucleotide Phosphate -- Glycosaminoglycans, Proteoglycans, and Glycoproteins -- Dietary Lipid Metabolism -- Fatty Acid, Triacylglycerol, and Ketone Body Metabolism -- Phospholipid, Glycosphingolipid, and Eicosanoid Metabolism -- Cholesterol, Lipoprotein, and Steroid Metabolism -- Amino Acids : Nitrogen Disposal -- Amino Acids : Degradation and Synthesis -- Amino Acids : Conversion to Specialized Products -- Nucleotide Metabolism -- Metabolic Effects of Insulin and Glucagon -- The Feed-Fast Cycle -- Diabetes Mellitus -- Obesity -- Nutrition : Overview and Macronutrients -- Micronutrients : Vitamins -- Micronutrients : Minerals -- DNA Structure, Replication, and Repair -- RNA Structure, Synthesis, and Processing -- Protein Synthesis -- Regulation of Gene Expression -- Biotechnology and Human Disease -- Blood Clotting.
Preceded by Biochemistry / Denise R. Ferrier. Seventh edition. [2017]
Includes bibliographical references and index.
Keywords: Biochemistry